(untitled) (Al-Farooq Journal of Sciences, 2026)
This research aims to bridge the knowledge gap in Libyan historiography by shifting from the traditional military narrative of Italian concentration camps (1929-1934) to an analysis of their sociological dimensions. It focuses on monitoring the systematic deconstruction of tribal units and analyzing the impact of pastoral collapse in creating structural poverty. Furthermore, it explores the role of unity of pain behind barbed wire in merging narrow affiliations and forging a unified national identity, while highlighting the value shifts and new roles imposed by the ordeal, particularly the role of women as guardians of memory and values. The research used an integrative methodology that combines the historical method to trace the context of forced displacement and colonial policies, and the descriptive-analytical method to dissect the complex social phenomena within the camp society. The study relied on qualitative tools, including content analysis of official documents and memoirs, and the interrogation of archived oral histories, while utilizing folk poetry (Ghanawi and Shatawi) as a sociological document reflecting the collective conscience and emotional memory of disease, hunger, and loss. The research found that the camps were laboratories for social genocide that caused a massive demographic rift and transformed Libyan society from an independent pastoral economy into a state of humiliating dependency. The results also proved that the shattering of traditional tribal structures was met with the birth of a unified national identity formed within the crucible of shared suffering. The research recommended the necessity of internationalizing the issue of the concentration camps as a full-fledged crime of genocide and integrating the history of victims and folk sociology into educational curricula. It also urged the launching of a national project for the digital archiving of camp sites and conducting interdisciplinary studies linking the trauma of the camps to the contemporary social and political behavior of Libyans.